Awareness in the context of prevalence of vitamin A deficiency among households in Western Kenya using a cross-sectional study - Oyunga, M.A.; Omondi, Dennis O.; Grant, F. (Science Publishing Group, 2016)
Increasing awareness of the role of vitamin A (VA) in human health has led to international efforts to eliminate VA deficiency (VAD) as a public health problem. This paper examined community awareness of existence, signs and symptoms, causes, control of VAD as well as attitudes, so as to identify knowledge gaps among health workers and caretakers/mothers. This was a community-based study within the catchment areas served by health facilities offering antenatal care services in Busia and Bungoma counties in Western Kenya. The study adopted cross-sectional design and purposive sampling technique. Eight focus group discussions (FGDs) were conducted with pregnant and lactating mothers and eight key informant interviews with those in charge of health facilities until saturation. Data was audio recorded, transcribed, coded and thematically analyzed using ATLAS.ti version 6 software. Most respondents stated having heard about VA/VAD but very few had the correct knowledge of signs and symptoms, causes, and control of VAD. Their attitudes towards VAD and its control were generally indifferent with a general belief that they had no control over their circumstances to reduce VAD. Although VAD was prevalent in the study area, majority of the people in the community had low awareness. This study, therefore, stresses the need for health education to raise community’s awareness on VAD in such settings in order to augment prevention, control and elimination efforts.